Nanogold-Loaded sharp-edged carbon bullets as plant-gene carriers - Vijayakumar, Periyasamy S.; Othalathara U. Abhilash; Khan, Bashir Mohammad; Bhagavatula L. V. Prasad (Advanced Functional Materials, 2010)
The higher DNA delivery efficiency into plants by gold nanoparticles embedded in sharp carbonaceous carriers is demonstrated. These nanogold-embedded carbon matrices are prepared by heat treatment of biogenic intracellular gold nanoparticles. The DNA-delivery efficiency is tested on a model plant, Nicotiana tabacum, and is further extended to the monocot, Oryza sativa, and a hard dicot tree species, Leucaena leucocephala. These materials reveal good dispersion of the transport material, producing a greater number of GUS foci per unit area. The added advantages of the composite carrier are the lower plasmid and gold requirements. Plant-cell damage with the carbon-supported particles is very minimal and can be, gauged from the increased plant regeneration and transformation efficiency compared with that of the commercial micrometer-sized gold particles. This is ascribed to the sharp edges that the carbon supports possess, which lead to better piercing capabilities with minimum damage.